Microscopic Effect of Mixed Wetting Capillary Characteristics on Spontaneous Imbibition Oil Recovery in Tight Reservoirs - Yu Pu; Erlong Yang; Di Wang (Energies)
The understanding of the mechanisms that govern water spontaneous imbibition in mixed wetting capillary channels plays a significant role in operating the oil extraction and energy replenishment for the tight oil reservoirs. In this work, the conservative form phase-field model together with the Navier–Stokes equation is employed to investigate the influence of the mixed wetting distribution and the wetting degree on the imbibition oil recovery effects and microscopic flow characteristics. Results indicate that there exist different oil detachment modes of spontaneous imbibition, and these modes are determined by the coupled effect of mixed wetting fraction and contact angle size. For the mixed wetting capillary with strong oil wetting, when fw is low, spontaneous imbibition can only partially detach the oil. Low fw slows down the fluid flow velocity and leads to the small imbibition oil recovery rate. After that, the influence of the surface contact angle size of the mixed wetting capillary is discussed. For the complete detachment mode, the capillary tube presents a form of water phase saturated filling, achieving the optimal imbibition oil recovery effect. For the mixed wetting capillary tube with the combination of weak water wetting and strong oil wetting (i.e., θw = 75° and θo = 165°), local spontaneous imbibition turbulence can only detach very little oil at the inlet of the water wetting area, ultimately achieving a recovery efficiency of less than 10%. This work illuminates the spontaneous imbibition oil recovery mechanisms and flow potentiality for the different mixed wetting capillary channels.